2006
DOI: 10.1103/physrevstab.9.063502
|View full text |Cite
|
Sign up to set email alerts
|

In situcleaning of metal cathodes using a hydrogen ion beam

Abstract: Metal photocathodes are commonly used in high-field rf guns because they are robust, straightforward to implement, and tolerate relatively poor vacuum compared to semiconductor cathodes. However, these cathodes have low quantum efficiency (QE) even at UV wavelengths, and still require some form of cleaning after installation in the gun. A commonly used process for improving the QE is laser cleaning. In this technique the UV-drive laser is focused to a small diameter close to the metal's damage threshold and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 9 publications
3
38
0
1
Order By: Relevance
“…It is well known that the work function is sensitive to crystal structure and perfection, and ion bombardment damage can produce work function reduction on the order of several hundred meV [40,41]. The low work function in our experiment may be caused by the aggressive ion bombardment during rf breakdowns, and is also supported by the highest QE for copper measured at this wavelength [37].…”
Section: Experiments Results and Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…It is well known that the work function is sensitive to crystal structure and perfection, and ion bombardment damage can produce work function reduction on the order of several hundred meV [40,41]. The low work function in our experiment may be caused by the aggressive ion bombardment during rf breakdowns, and is also supported by the highest QE for copper measured at this wavelength [37].…”
Section: Experiments Results and Discussionsupporting
confidence: 64%
“…The copper cathode QE rose by a factor of $3:5 to 10 À4 after gun conditioning, which is the highest QE reported at this wavelength for a copper cathode [37]. The increase of the cathode QE during gun conditioning is also observed in other groups [5,38], which indicates gun conditioning along with rf breakdowns or high intensity UV laser illumination on the cathode has similar effects as ion cleaning or laser cleaning [37,39]. The QE fitting to Eq.…”
Section: Experiments Results and Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…From the same 3-step based photoemission model, it can be shown that the quantum efficiency (QE) is proportional to the square of the excess energy [12]. In the past decade, experimental studies of metal cathodes with normally incident light have validated this model both in terms of QE [12] and emittance [11,13,14]. A consequence of this model is that the QE depends on the 4th power of the emittance that is required.…”
mentioning
confidence: 94%
“…The spectrum is not corrected for spectral transmittance. (b) Photoelectron yield quantum efficiencies for aluminium, stainless steel, gold [5] and copper [6].…”
Section: Introductionmentioning
confidence: 99%